Interactive Effects of Zinc, Copper and Manganese in Diets for Broilers - Shelton, J.L.; Southern, L.L. (International Journal of Poultry Science, 2007)
An experiment was conducted to determine the interactive effects of Zn, Cu and Mn addition to diets of 0 to 14-d old broilers on growth performance, bone breaking strength, bone ash percentage and tissue mineral concentrations. Two levels of Zn (0 or 75 ppm, as Zn sulfate), 2 levels of Mn (0 or 100 ppm, as Mn sulfate) and 2 levels of Cu (0 or 7 ppm, as Cu sulfate) were supplemented to corn-soybean meal diets in a 2×2×2 factorial arrangement. Each treatment had 6 replications with 5 chicks each and the initial and final BW were 46 and 382 g. Daily gain, daily feed intake, gain:feed, bone breaking strength and bone and pancreatic Zn concentrations were increased (p<0.05) in chicks fed diets with supplemental Zn. Bone, liver and pancreatic Mn levels were increased (p<0.01) in chicks fed diets with supplemental Mn. Bone breaking strength was increased when Zn was added to the diets with or without Cu addition, but the increase was greater in chicks fed the diets without Cu addition (Zn×Cu, p<0.05). Bone ash percentage was increased in chicks fed the diets with Zn, Mn, or Cu addition but the increase was not additive (Zn×Mn×Cu, p<0.03). Liver Cu level was increased (p<0.01) in chicks fed diets with Cu addition. Bone and liver Cu levels were decreased (p<0.05) in chicks fed diets with Zn addition. Bone and pancreas Fe levels were decreased (p<0.05) in chicks fed diets with added Zn. Bone Zn level was decreased (p<0.03) in chicks fed diets with added Cu. Liver and pancreatic Mn levels were increased (p<0.05) in chicks fed diets with added Zn. This study indicates that Zn addition is necessary for normal growth and bone strength of chicks and that Zn addition had negative effects on tissue Cu and Fe levels and a positive effect on tissue Mn levels.